Single-cell biomagnifier for optical nanoscopes and nanotweezers - Li, Yuchao (Light Sci Appl, 2019)
Optical microscopes and optical tweezers, which were invented to image and manipulate microscale objects, have revolutionized cellular and molecular biology. However, the optical resolution is hampered by the diffraction limit; thus, optical microscopes and optical tweezers cannot be directly used to image and manipulate nano-objects. The emerging plasmonic/photonic nanoscopes and nanotweezers can achieve nanometer resolution, but the high-index material structures will easily cause mechanical and photothermal damage to biospecimens. Here, we demonstrate subdiffraction-limit imaging and manipulation of nano-objects by a noninvasive device that was constructed by trapping a cell on a fiber tip. The trapped cell, acting as a biomagnifier, could magnify nanostructures with a resolution of 100 nm (λ/5.5) under white-light microscopy. The focus of the biomagnifier formed a nano-optical trap that allowed precise manipulation of an individual nanoparticle with a radius of 50 nm. This biomagnifier provides a high-precision tool for optical imaging, sensing, and assembly of bionanomaterials.